MENINGKATKAN E-LEARNING ANTARA DOSEN DAN MAHASISWA MELALUI METODE KONFERENSI VIDEO - Debora Manalu (JURNAL PENDIDIKAN ROKANIA, 2022)
At this time the Government and the Minister of education are construct to all aducational institutions in Indonesia to do E-Learning. As for the implementation that is recommended implementation is to do the learning process from home. The learning process carried out at home must have an important rolet to increase knowledge and skills in order to achieve learning objectives in accordance with the applicable curriculum. But these activities have several obstacles for educators and students, not only in schools, higher education also occurs. Lecturers and students have several obstacles in conducting the learning process through E-Learning. As for the obstacles that occur are the network that is not good or slow, laptop/handphone/internet package facilities that are less supportive, disruptions from family talks whwn conduting video conferences, learning materials shared in E-Learning sometimes do not appear, and physical/student faces are not raised in E-Learning, so the learning process is not carried out conducive and effective. For the authors try to explain how to improve the learning process through video conferencing based on literature study methods with the case studies that occur in higher education through learning Christian Religious Education conducted by lecturers and students at Indonesian Christian Universities.